2009
DOI: 10.1111/j.1364-3703.2009.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

An artificial chimeric derivative of Citrus viroid V involves the terminal left domain in pathogenicity

Abstract: The recently described Citrus viroid V (CVd-V) induces, in Etrog citron, mild stunting and very small necrotic lesions and cracks, sometimes filled with gum. As Etrog citron plants co-infected with Citrus dwarfing viroid (CDVd) and CVd-V show synergistic interactions, these host-viroid combinations provide a convenient model to identify the pathogenicity determinant(s). The biological effects of replacing limited portions of the rod-like structure of CVd-V with the corresponding portions of CDVd are reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Earlier attempts failed to transfer CVd-V or its artificial chimers to herbaceous plants (Serra et al, 2009). However, evidence of de novo replication of Australian grapevine viroid and apple scar skin viroid (type member of the Apscaviroid) in several herbaceous plants have been reported (Rezaian, 1990;Zakiaghl and Izadpanah, 2010;Walia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier attempts failed to transfer CVd-V or its artificial chimers to herbaceous plants (Serra et al, 2009). However, evidence of de novo replication of Australian grapevine viroid and apple scar skin viroid (type member of the Apscaviroid) in several herbaceous plants have been reported (Rezaian, 1990;Zakiaghl and Izadpanah, 2010;Walia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results reported here on the modulation of symptom expression in CEVd‐infected Etrog citron plants show the same trend as those described for PSTVd. It was also observed that CEVd COL ‐infected plants displayed extremely subtle leaf distortion, suggesting that other positions of the viroid molecule may also play a role in the modulation of symptom expression, as already reported for the T L , T R and C domains of PSTVd (Qi and Ding, 2003; Sano et al ., 1992) and for the T L domain of Citrus viroid V (CVd‐V) and Citrus dwarfing viroid (CDVd), two members of the genus Apscaviroid (Murcia et al ., 2009a; Serra et al ., 2009).…”
mentioning
confidence: 99%